2002
DOI: 10.1097/00002030-200201250-00010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of HIV-1 genotyping and expert advice: the Havana trial

Abstract: HIV-1 genotyping interpreted by a software package improves the virological outcome when it is added to the clinical information as a basis for decisions on changing antiretroviral therapy. The expert advice also showed virologic benefit in the second failure group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
199
1
8

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 284 publications
(215 citation statements)
references
References 26 publications
7
199
1
8
Order By: Relevance
“…Nevertheless, the advantage of genotyping information was lost after 12 months. These findings were similar to results from previous randomized studies [5][6][7][8][9], indicating that resistance testing helps to choose more effective regimens in patients failing previous antiretroviral regimens. Although group 2 patients had fewer mutations and viral samples with no mutations (wild type virus, Table 5), this group received less active drugs (Figure 2), thus emphasizing the importance of genotyping in salvage therapy.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Nevertheless, the advantage of genotyping information was lost after 12 months. These findings were similar to results from previous randomized studies [5][6][7][8][9], indicating that resistance testing helps to choose more effective regimens in patients failing previous antiretroviral regimens. Although group 2 patients had fewer mutations and viral samples with no mutations (wild type virus, Table 5), this group received less active drugs (Figure 2), thus emphasizing the importance of genotyping in salvage therapy.…”
Section: Discussionsupporting
confidence: 88%
“…Among others, the GART [6] and the NARVAL [7] studies demonstrated the usefulness of HIV genotyping, compared to phenotyping. The Argenta [8] and Havana [9] studies evaluated the effects of compliance and expert advice on HIV-1 genotyping.…”
mentioning
confidence: 99%
“…Similar results were obtained in another prospective study where 326 HIV-1-infected patients on stable ART and with treatment failure were randomized to receive salvage ART guided by GRT (161 patients) versus salvage ART guided by clinical judgment (165 patients). The proportion of patients with plasma HIV-1 RNA <400 copies/mL at 24 weeks was lower for those guided by GRT than for those guided by clinical judgment (48.5 and 36.2%, respectively; P < 0.05) (10). In addition, these two studies have suggested that the benefit of resistance testing is increased when expert interpretation of the resistance test results is used to guide therapy changes (8,10).…”
Section: Discussionmentioning
confidence: 97%
“…No benefit regarding the clinical parameters was observed in those patients submitted to ART change based on the routine access to HIV-1 genotype testing associated with expert recommendations when compared to those patients whose ART had been changed based on their previous history of ART use. Several previously published prospective studies have shown a benefit associated with resistance testing (8)(9)(10)20). In a prospective controlled trial, 153 HIV-1-infected patients failing on combination drug regimens were randomized to receive salvage ART guided by GRT with expert advice (78 patients) versus salvage ART guided by clinical judgment (75 patients).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation